Neurobiology of Aggressive Behavior—Role of Autoantibodies Reactive With Stress-Related Peptide Hormones - Vaeroy, Henning; Schneider, Frida; Fetissov, Sergueï O. (Frontiers in Psychiatry, 2019)
Adrenocorticotropic hormone together with arginine vasopressin and oxytocin, the neuropeptides regulating the stress response and the hypothalamic-pituitary-adrenal axis activity, are known to modulate aggressive behavior. The functional role of the adrenocorticotropic hormone immunoglobulin G autoantibodies in peptidergic signaling and motivated behavior, including aggression, has been shown in experimental and in vitro models. This review summarizes some experimental data implicating autoantibodies reactive with stress-related peptides in aggressive behavior.